2001
DOI: 10.1177/0899764001302010
|View full text |Cite
|
Sign up to set email alerts
|

Financial Vulnerability among Arts Organizations: A Test of the Tuckman-Chang Measures

Abstract: In the past decade, nonprofits scholars have given increased attention to the topic of vulnerability and organizational demise. An early contribution to this literature wasFinancial distress is a common condition for many nonprofit organizations. Grants run out, or funders change their giving guidelines. Individual donor preferences change, or contributions are diverted to competing organizations. Government support declines, increases, and declines again. Sometimes, legal conflicts or fiscal mismanagement cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
248
3
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(268 citation statements)
references
References 17 publications
4
248
3
4
Order By: Relevance
“…A financially flexible NPO is one with access to equity balance (assets higher than liabilities), many revenue sources, administrative costs which could be cut without affecting programs' administration, and positive operating margins. Hager (2001) found that although those measures do not apply to all NPOs, they are good predictors of their survival or closure. Trying to encompass various measures we will call this dimension Financial Flexibility and Resource acquisition.…”
Section: 322mentioning
confidence: 91%
“…A financially flexible NPO is one with access to equity balance (assets higher than liabilities), many revenue sources, administrative costs which could be cut without affecting programs' administration, and positive operating margins. Hager (2001) found that although those measures do not apply to all NPOs, they are good predictors of their survival or closure. Trying to encompass various measures we will call this dimension Financial Flexibility and Resource acquisition.…”
Section: 322mentioning
confidence: 91%
“…However, as Lecy et al (2011) [94] have shown, rigorous impact assessment is rare in NPOs due to a lack of good impact indicators. In addition to mission completion, good financial performance has become more relevant to NPOs during the past decades [95,96]. Furthermore, commercialization of the non-profit sector has increased [97,98].…”
Section: Accounting Ratios Rejectedmentioning
confidence: 99%
“…Alexander, 1998;Baum & Singh, 1996;Galaskiewicz & Bielefeld, 1998); new organizations are founded (Chambré, 1995); and existing organizations merge or die (Hager, 2001). The process of new births is particularly critical at the current time.…”
Section: The Number Of New Nonprofit Organizations Has Grown Considermentioning
confidence: 99%